Design of planar-zigzag semiconducting polymers to control chain orientation and electronic structure for organic photovoltaics. (8th September 2022) - Chen, Fengkun; Nakano, Kyohei; Kaji, Yumiko; Tajima, Keisuke
Abstract : The planar-zigzag shape of polymers leads to a face-on orientation of the main chains in thin films which improves the photovoltaic performance through better absorption coefficients, charge carrier generation, and collection efficiency. Abstract : A series of π-conjugated copolymers containing V-shaped electron-deficient units of triphenyleno[1, 2- c :7, 8- c ′]bis([1, 2, 5]thiadiazole) (TPTz) or its non-fused precursor were synthesized. Both the ring fusion in TPTz and the appropriate spacer units between TPTz and the donor unit were important for allowing the polymers to adopt a planar-zigzag shape as the stable chain conformation. The planar-zigzag shape of the polymers strongly affected their anisotropic electronic and electrical properties in thin films, and in particular, the face-on orientation increased not only the absorption coefficients but also the charge carrier generation and collection efficiency, resulting in improved photovoltaic performance in mixed bulk heterojunction films with an electron acceptor.